MODEL OF FUNCTIONING OF THE TECHNOLOGY OF DELIVERY OF SPARE PARTS BY A TRANSPORT AND LOGISTICS CENTER ON THE BASIS OF CLUSTERING - Pavlenko, O.; Boyko, A. (Municipal economy of cities. Series: «Economy science», 2025)
The article analyzes the current state and prospects for the development of the technology for the delivery of spare parts by a transport and logistics center. This allowed us to formulate the purpose of the study in this development. This topic is relevant, since the effective organization of the delivery of spare parts by a transport and logistics center will allow many transport companies to build a sustainable system of cargo transportation throughout the country. It is the creation of clusters of transport and logistics companies that will make it possible to save costs by sharing resources and information. It will also help to increase the productivity of services for most customers. The study determines that the development of logistics clusters not only motivates the geographical concentration of different types of logistics companies, but also triggers the exit of organizations operating at different stages of the supply chain. The article develops a structural model of interaction in the spare parts delivery system, which is formed as a system that includes subsystems of suppliers (in Ukraine, from abroad); subsystem of customers (regular: retail and wholesale; one-time); subsystems of transport and logistics companies of suppliers and customers. A separate subsystem of the delivery cluster has been selected, which is presented in the form of a structural model of interaction of the subsystem for the delivery of spare parts from abroad by order of a wholesale regular customer. Two options for organizing delivery have been identified: the first - only with the participation of the transport and logistics center of the company “ALL TRUCK PARTS” and the second with the participation of the supplier's transport and logistics company. On the basis of the proposed options, models of the technology for the delivery of spare parts by transport and logistics centers have been built, which take into account the specifics of performing sequential technological operations. The prospect of using these models will allow for a statistical analysis of the values of the influence parameters (time of operations, order volumes and transportation distances), simulation using the developed software environment and determining the optimal conditions for the functioning of the cluster organization of spare parts delivery by a transport and logistics center.